Depth-dependent response of soil aggregates and soil organic carbon content to long-term elevated CO2 in a temperate grassland soil. (August 2018) - Keidel, L.; Lenhart, K.; Moser, G.; Müller, C.
Abstract: Facing rising atmospheric CO2 concentrations, subsoils may play an important role in the global carbon (C) cycle due to the presence of unsaturated mineral surfaces. Further, macroaggregation is considered a crucial process influencing C sequestration. However, analyses on subsoil aggregation and C retention processes under long-term elevated CO2 (eCO2 ) are lacking. In this study we investigated the long-term effect of +20% above ambient CO2 concentration (corresponds to conditions reached 2035–2045) in a temperate grassland ecosystem at the Giessen Free Air CO2 Enrichment (Gi-FACE), Germany. A depth-dependent response of macroaggregation to eCO2 was observed: While in subsoil (15–45 cm depth) macroaggregation increased under eCO2, no CO2 induced change in macroaggregation was detected in topsoil (0–15 cm). Increased macroaggregation in subsoil coincided with higher SOC content of large macroaggregates (LM). Mean residence time (MRT) of SOC in aggregate-size classes were not different among each other under eCO2 . However, macroaggregates and bulk soil differed in their MRT between soil depths. Despite increased macroaggregation and an estimated high SOC sequestration potential in subsoil we could not observe an increase in SOC content of bulk soil. Highlights: Long-term eCO2 increased macroaggregation in subsoil but not in topsoil. Long-term eCO2 did not change total SOC content. Mean residence time (MRT) of SOC was similar among aggregate-size classes under eCO2 . MRT of SOC in macroaggregates and bulk soil was greater in sub-than topsoil.